Forensic Feature Exploration and Comprehensive Genetic Insights Into Yugu Ethnic Minority and Northern Han Population via a Novel NGS-Based Marker Set - Lan, Qiong; Zhao, Congying; Chen, Chong; Xu, Hui; Fang, Yating; Yao, Hongbing; Zhu, Bofeng (Frontiers in Genetics, 2022)
Introduction of MPS technology has expanded the potential applications of groups of DNA markers and increased the discrimination power by taking variations in the flanking regions of targeted loci into consideration. Here, a collection of nuclear and extranuclear DNA markers (totally 355 genetic markers and mtDNA) were assessed comprehensively and systematically for polymorphism detections, and genetic background dissections in Yugu ethnic group from Gansu province (Yugu) and Han population from Inner Mongolia Autonomous Region of China (NMH). Assembling of individual informative SNPs, ancestry informative SNPs and phenotype informative SNPs indicated that elevated efficiencies of the marker set in separating full sibling and challenging half sibling determination cases in parentage tests, predicting ancestry origins of unknown individuals from at least four continental populations and providing informative characteristic-related clues for Chinese populations were highlighted in the present study. Demographic history analysis based on mtDNA control region also implied that population expansions may have occurred in these two populations during LGM (Yugu), early Holocene (NMH) and the Late Pleistocene (NMH). To sum up, genetic insights from the perspectives of autosomal DNA, Y chromosomal DNA and mtDNA yielded that Yugu ethnic group was genetically closer related to the Han population of northern origin. But considering the complex development and formation process of the Yugu group, we admitted that more relevant groups (like Mongolian, Tibetan, Hui and Tu) were encouraged to be analyzed and compared to gain a refined genetic composition picture of the Yugu group in future work.